Treatment resistant psychosis in children and adolescents and clozapine: Nuances - Pattnaik, Jigyansa Ipsita; Panda, Udit Kumar; Chandran, Suhas; Padhy, Susanta; Ravan, Jayaprakash Russell (Frontiers in Psychiatry, 2023)
With the proliferation of research on high-risk psychosis spectrum diseases, it is crucial to distinguish a prodrome or psychosis-like episode in children and adolescents from true psychosis. The limited role of psychopharmacology in such circumstances is well documented, underlining the difficulties in diagnosing treatment resistance. To add to the confusion is emerging data on the head-to-head comparison trials for treatment-resistant and treatment-refractory schizophrenia. Clozapine, the molecule typically used for resistant schizophrenia or otherwise psychotic pathology has no FDA or manufacturer guidelines for use in the pediatric population. Possibly due to developmental pharmacokinetic (PK) considerations, clozapine-related side effects may be more common in children than in adults. Despite evidence of an increased risk for seizures and haematological problems in children, clozapine is widely used off-label. Clozapine reduces the severity of untreated early onset schizophrenia, aggressive or suicidal behaviour, and severe nonpsychotic illness. There is inconsistent prescribing, administration, and monitoring of clozapine, and limited database evidence-backed guidelines. Despite the overwhelming efficacy, problems remain regarding unambiguous indications of use and risk-benefits assessments. This article reviews the nuances in the diagnosis of treatment resistance psychosis in childhood and adolescents and its management, in particular highlighting the evidence base for clozapine in this population group.